Total factor productivity growth of Vietnamese enterprises by sector and region: Evidence from panel data analysis - Hai Quang Nguyen (Economies, 2021)
Total factor productivity growth (TFPG) is an important indicator evaluating the enterprise development model. The aim of this study is to consider the imbalance between TFPG and enterprises growth patterns of sectors and regions in Vietnam. The results of panel data analysis in 2005-2018 show that the growth of Vietnamese enterprises is mainly due to increased capital, especially in the non-state enterprise sector and in the Red River Delta. Total factor productivity (TFP) was found to be present in the non-state and inward foreign investment sectors during the five years 2014-2018. By comparison, the state-owned enterprise sector fell sharply during the same period. Strong upward increases in TFP were notable in the Northern Midlands and Mountain areas, the Mekong River Delta, and the Southeast, while there was a marked downward trend in the Central Highlands and the Red River Delta, especially marked in the Central Highlands. Thus, the results from this study are a basis to suggest an appropriate policy mix that helps to improve the performance of enterprises in different sectors and regions of Vietnam.
Keywords: 330; enterprise sectors; enterprises in regions; panel data analysis; total factor productivity growth